PENGARUH RASIO LIKUIDITAS, LEVERAGE, DAN AKTIVITAS TERHADAP PROFITABILITAS PADA PERUSAHAAN FARMASI YANG TERDAFTAR DI BEI TAHUN 2009-2013 - B31111053, ATIKA (Jurnal Manajemen Update, 2016)
This study aims to examine and explain the effect of the liquidity ratios, leverage, and activity on the level of profitability is partially and simultaneously. Which in this study liquidity ratios indicated by the Current Ratio, the leverage ratio is indicated by Debt To Equity Ratio and the ratio of activity indicated by Total Asset Turn Over. The population in this study are the companies listed on the Indonesian Stock Exchange (BEI) in the period 2009-2013. Samples were collected as much as 9 pharmaceutical company chosen by purposive sampling technique. The independent variable in this study is liquidity (Current Ratio), Leverage (Debt to Equity Ratio), activity (Total Asset Turnover), and while the dependent variable is Profitability (Return on Equity). Methods of analysis of this study using multiple regression analysis. The results showed that the Liquidity positive and significant impact on profitability, leverage and no significant negative impact on profitability, and activity and no significant positive effect on profitability. The coefficient of determination is 76.2%. This result indicates that the magnitude of the ability of independent variables in explaining the dependent variable while 23.8% is explained by other variables. Keywords: Liquidity, Leverage, Activity and Profitability